Evergreen talent : a guide to hiring and cultivating a sustainable workforce - Matuson, Roberta Chinsky (Career Press, 2020)
"This book will show you how any company can attract, find, and keep employees for the long-term. What many organization leaders fail to understand is that you can't simply transplant a competitor's talent strategy and achieve the same results-conditions are different. A company that takes the time to examine its own environment, select talent accordingly, and nurture its people will prevail, regardless of economic conditions"--